Black Catholicism in Mexico - Bristol, Joan C. (Journal of Africana religions, 2014)
Mexico provides an example of African American Christianity that seems both familiar and unfamiliar within the context of the Americas. It is almost impossible to trace African elements in Mexican Catholicism in the way that we can in other parts of the diaspora, yet African American Christianity existed in colonial Mexico and influenced what we see as Mexican Catholicism today. [End Page 255] Mexicans of African descent formed religious communities around African or Black identities and used ritual practice in distinctive ways that were tied to their lives as slaves and servants. Ritual practice also allowed Africans and their descendants to participate in colonial Catholic society through their roles as healers and their membership in confraternities and attendance at church services.